Perencanaan Kebutuhan Bahan Baku pada Produksi Bak Dropside Truk Studi Kasus di CV. Karya Cipta Baru - Rama Permadi; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV. Karya Cipta Baru is a commercial vehicle manufacturing company that CV. Karya Cipta Baru is a company engaged in the construction of commercial vehicles, with a primary focus on the production of various types of truck beds, particularly dropside truck beds. This study aims to analyze raw material requirements planning and assess inventory costs and potential losses resulting from unfulfilled orders in a make-to-order system. The methods applied include Lot-for-Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The data used in this study includes product demand, raw material requirements, ordering costs, storage costs, and production loss costs. The research findings indicate that the LFL method yields the lowest total inventory cost, namely Rp3,625,965, compared to EOQ at Rp7,344,000 and POQ at Rp6,440,686. Additionally, the total cost of stock shortages, amounting to Rp2,304,000, stems from overtime expenses and penalties resulting from delays in fulfilling orders. Therefore, the LFL method is considered the most efficient in reducing inventory costs and the risk of customer dissatisfaction related to order fulfillment.